Tiktok-Based Multimedia on Climate Change Material in Science Lessons in Junior High School - Darmilus; Hartono; Syarifuddin (Universitas Pendidikan Ganesha, 2025)
The current reality is that many learning activities have not been implemented effectively. Therefore, the purpose of this study is to develop TikTok-Based Multimedia on Climate Change Material in Science Learning in Junior High Schools. This type of research is development research using the Alessi and Trollip development model. The subjects of the study were grade VII junior high school students. The validation stages of the expert team's evaluation included learning design experts, learning media experts, and language experts. Data collection techniques in this study were observation, interviews, student needs questionnaires, walkthroughs, and tests. The instruments used in this study included media validation sheets, practicality instruments, and assessment tools. The data analysis techniques used were qualitative and quantitative descriptive analysis. The results of the study were the validity of the material, language, and media design aspects, each scoring 87%, 89%, and 93%, indicating high feasibility. Practicality was tested through one-on-one sessions, small groups, and field tests, with scores of 83.83% and 85.63%, respectively. The effectiveness of multimedia can be seen from the increase in student learning outcomes, with an average pretest score of 51.61% to a posttest of 86.61% and an N-Gain value of 0.72. It is concluded that TikTok-based multimedia is a valid, practical, and effective learning tool, providing an interesting approach to improving students' understanding of climate change in science education. These findings prove that TikTok-based multimedia is an educational tool that offers a dynamic and engaging approach to improving students' understanding of the concept of climate change in science education.